P-wave velocity structure and implications for magmatism and metallogenesis in the southern Altaids: Constraint from wide-angle seismic data along the Altai-Eastern Tianshan traverse - Bai, Zhiming; Zhao, Liang; Xiao, Wenjiao; Xu, Tao; Badal, José (Frontiers in Earth Science, 2023)
Altaids in the Central Asian Orogenic Belt (CAOB) is one of the world's largest orogenic belts containing mineral deposits. Together with the Junggar terrain they open an important window to study the Paleozoic tectonic evolution of the CAOB. In this paper, we analyze a 637-km-long wide-angle refraction/reflection seismic profile across the Altai-Eastern Tianshan orogenic belt in the southern Altaids, conducted in September 2018 using 10 large explosive charges fired in drilled holes. We use a traveltime inversion method to reconstruct the lithospheric P-wave velocity structure along the profile. The lithosphere is composed of a 43-55-km-thick crust, a ~10-km-thick crust-mantle transition layer beneath the Altai Mountain, and a ~25-km-thick layer of lithospheric mantle. The results clearly reveal: a prominent Moho uplift beneath the Yemaquan Island Arc, two major crustal-scale low-velocity anomalies (LVAs) beneath the Yemaquan Arc and Bogda Mountain, and three high-velocity anomalies (HVAs) near the surface around the Kalatongke, Yemaquan and Kalatage mining areas. We hypothesize that the subduction of the Paleo-Asian Ocean occurred with strong mantle upwelling. We suggest that continued compression of the Paleo-Asian Ocean causes the delamination of lithosphere, as well as asthenospheric material upwelling and magma underplating into the crust. Consistently, Paleozoic mafic-ultramafic rocks and mantle-derived minerals related to gold, copper and nickel deposits, are widely extended in the area. Our results show that the P-wave velocity-depth curves for deeper depths (> 30 km) in the southern Altai and Junggar Basin are close to those of the continental arcs and global continent average. Despite powerful Paleozoic subduction activity, orogeny and volcanism strongly modified the lower crust in the region, part of ancient continental crust was still preserved below the southern Altai and Junggar Basin. In addition, the upper part (depth 5-30 km) of the velocity-depth curve for the Junggar Basin is close to that of the Costa Rica volcanic front and the British Columbia accreted terrain, suggesting that Paleozoic orogenic activity has intensively reconstructed the upper-middle crust beneath the Junggar Basin.